Answer:
(3, 2)
Step-by-step explanation:
Given the 2 equations
y = 2x - 4 → (1)
3x + y = 11 → (2)
Substitute y = 2x - 4 into (2)
3x + 2x - 4 = 11
5x - 4 = 11 ( add 4 to both sides )
5x = 15 ( divide both sides by 5 )
x = 3
Substitute x = 3 into (1) for corresponding value of y
y = (2 × 3) - 4 = 6 - 4 = 2
Solution is (3, 2)
Answer:
√50= 5√2
Step-by-step explanation:
50=25*2
√50=√25*2
√50=√5*5*2
√50= 5√2
3d=12
This should be your equation
And if it is asking for the answer it would be 4
I hope this answer helps!
Answer:
A. 6.9
Step-by-step explanation:
Edge 2020